The role of veterinary drug use in driving antimicrobial resistance of Staphylococcus aureus isolates in smallholder swine farms in Central Vietnam - Nguyen Van Chao; Ho Thi Dung; Vu Thi Thanh Tam; Phan Thi Hang; Bui Thi Hien (Open Veterinary Journal)
Background: Staphylococcus aureus is a well-known opportunistic pathogen widely present in humans and food-producing animals. The emergence of antimicrobial resistance (AMR) in S. aureus represents a major challenge to animal and public health. Poor biosecurity practices and the misuse and overuse of veterinary drugs in farming settings may apply environmental pressure, which favors the selection of AMR bacteria.